Hubungan Pengetahuan dengan Sikap Pemeliharaan Kesehatan Gigi pada Siswa SMP Negeri di Kecamatan Medan Denai - Zulfi Amalia Bachtiar; Ayu Augustine Novita (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Knowledge, attitude and behavior are the main factors that affect dental and oral health. Behaviors that arise due to lack of knowledge of children about the importance of maintaining oral health, causing a high prevalence of dental caries in school-age children. This aim of the study was to know the level of knowledge and attitudes of dental and oral health maintenance based on age and gender, and to analyze the relationship between knowledge and attitudes of oral health maintanance. This research is descriptive correlative with a cross-sectional design. The sampling technique is the proportional stratified random sampling. The measuring instrument of this research is a questionnaire. The results of the study on the level of knowledge and attitudes based on age and gender were mostly in good category with data analysis there was a significant relationship between the level of knowledge and age (p=0,048), there was no significant relationship between the level of knowledge and gender (p=0,952), there was There was a significant relationship between the level of attitude and age (p=0,000), there was a significant relationship between the level of attitude and gender (p=0,039), and there was no significant relationship between knowledge and attitudes of maintaining oral health (p = 0,066). The conclusion is the need for counseling so that the knowledge and attitude of maintaining oral health is in line with behavior in maintaining dental and oral health.